The hidden heritage of Arab libraries: Online catalogs and institutional barriers to discoverability. (December 2018) - Kurzman, Charles; Martin, John D.
Advances in technology have made access to information about library holdings a seemingly universal feature of interaction with modern libraries. However, this type of access does not exist evenly throughout the world. There is a vast "hidden heritage" contained in Arab libraries without online public access catalogs. This article reports and summarizes findings from research conducted as part of a year-long investigation into international library collaboration in Arab libraries. The research included: (a) a survey of online presence for Arab libraries, (b) a survey of Arab librarians, and (c) focused panel discussions with Arab librarians and library scholars. This study finds that the relatively small online presence of libraries cannot be explained by material factors alone: institutional factors also play an important role in keeping information about library collections offline.